Analysis of Fishing Business in the Biosphere Reserve of Giam Siak Kecil-Bukit Batu Village, Lubuk Gaung Sub-District, Bengkalis District, Riau Province - Erwandi, Dwi Putra Iqbal; Arief, Hazmi; Yulinda, Eni (Jurnal Perikanan dan Kelautan, 2024)
The Giam Siak Kecil—Bukit Batu Biosphere Reserve (GSKBB) is a UNESCO-designated protected area in Riau Province, Indonesia. Located within Bengkalis and Siak Regencies, GSKBB is renowned for its diverse ecosystems, including coastal wetlands, mangrove forests, and peatlands. To understand the economic viability of fishing activities within this biosphere reserve, a study was conducted in November 2023 in Siak Kecil District. The research focused on local fishermen using traditional fishing methods such as cast nets, lukah (traps), and hambat (scoops). Data analysis revealed that despite the environmental challenges faced by GSKBB, fishing remains a significant source of income for many local communities. The average investment made by fishermen was IDR 34,667,375, while annual revenue reached IDR 76,052,500. After accounting for costs such as fuel, equipment maintenance, and bait, fishermen realized an average profit of IDR 52,989,502 per year. The calculated revenue cost ratio (RCR) of 3.29, greater than 1, indicates a favorable financial performance for the fishing businesses in GSKBB. This suggests that the region's natural resources can sustainably provide a viable livelihood for local communities. However, it is essential to monitor the long-term sustainability of fishing practices to ensure the preservation of GSKBB's ecosystems and the continued economic well-being of its inhabitants.